Prevalence of intestinal parasites among inmates in Midwest Brazil - Curval, Larissa Gabrielle; Franca, Adriana de Oliveira; Fernandes, Henrique Jorge; Mendes, Rinaldo Poncio; Carvalho, Lidia Raquel de [UNESP]; Higa, Minoru German; Ferreira, Eduardo de Castro; Cavalheiros Dorval, Maria Elizabeth (Public Library Science, 2017)
Background Intestinal parasitic infections constitute a public health issue in developing countries, with prevalence rates as high as 90%, a figure set to escalate as the socioeconomic status of affected populations deteriorates. Investigating the occurrence of these infections among inmates is critical, since this group is more vulnerable to the spread of a number of infectious illnesses. Methods This cross-sectional, analytical, quantitative study was conducted in July 2015 at prison facilities located in Midwest Brazil to estimate the prevalence of parasitic infection among inmates. For detection of parasites, 510 stool samples were examined by ether centrifugation and spontaneous sedimentation. Results Eight parasitic species were detected, with an overall prevalence of 20.2% (103/510). Giardia lamblia and Entamoeba histolytica/dispar were the most frequent pathogenic parasites. Endolimax nana was the predominant non-pathogenic species. Nearly half of the subjects (53/103; 51.4%) were positive for mixed infection. Logistic regression revealed that inmates held in closed conditions were more likely to contract parasitic infections than those held in a semi-open regime (OR = 1.97; 95% CI = 1.19-3.25; p = 0.0085). A higher prevalence of parasitic infections was observed among individuals who had received no prophylactic antiparasitic treatment in previous years (OR = 10.2; 95% CI = 5.86-17.66; p < 0.001). The other factors investigated had no direct association with the presence of intestinal parasites. Conclusion Infections caused by directly transmissible parasites were detected. Without adequate treatment and prophylactic guidance, inmates tend to remain indefinitely infected with intestinal parasites, whether while serving time in prison or after release.